Incidence of wound dehiscence after keratoplasty: a meta-analysis of observational studies - Zheng, Na; He, Wenjing; Zhu, Siquan (Frontiers in Medicine, 2023)
Background: The comprehensive investigation of the association between keratoplasty and wound dehiscence remains limited, despite corneal disease being a leading cause of visual impairment.Methods: A meticulous search strategy was executed across prominent databases such as Web of Science, PubMed, Cochrane Library, and Embase. Data relevant to our research objective were extracted from eligible studies. The methodological quality of each study was assessed using the ROBINS-I tool, while statistical analysis was conducted utilizing STATA 17.0. To evaluate potential publication bias, the Funnel plot and Egger's test were employed.Results: A total of 11 articles were deemed suitable for inclusion in our analysis.Our findings indicate that the overall incidence of wound dehiscence following keratoplasty was estimated to be 1.9% (95% CI: 0.013, 0.026), although substantial heterogeneity was observed (I 2 =72.798%). Notably, developed countries exhibited a higher incidence of wound dehiscence compared to their developing counterparts. Furthermore, the occurrence of wound dehiscence was found to be lower in deep anterior lamellar keratoplasty (DALK) procedures when compared to penetrating keratoplasty (PK). Analysis utilizing Egger's linear regression method yielded no evidence of publication bias (p = 0.91).Moreover, within the first year post-keratoplasty, approximately 31.4% of patients experienced wound dehiscence (95% CI: 0.149, 0.503), and 43.1% exhibited a decline in best-corrected visual acuity (BCVA) (95% CI: 0.341, 0.522).The results of our study unveiled the occurrence rate of wound dehiscence following keratoplasty, exhibiting variations based on economic level and the specific surgical procedure employed. Furthermore, onset time of wound dehiscence and visual acuity warrant consideration.